2019
DOI: 10.18485/esptoday.2019.7.2.5
|View full text |Cite
|
Sign up to set email alerts
|

The Strategy Inventory for Second Language Learning: Tested, Adapted, and Validated in the Slovenian Higher Education Context

Abstract: In administering the Strategy Inventory for Language Learning (SILL) survey, our research focused on the use of second language learning strategies (SLLS) among higher education students, ascertaining what SLLS they use, the relationships between the strategies, and how the use of one group of SLLS can explain the use of other groups of strategies. This study examined the validity of the SILL (Oxford, 1990: 293-300) in a specific context by performing an exploratory and confirmatory factor analyses based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Bremner finds that compensation and metacognitive strategies were used most of all, while affective and memory strategies were the least used ones (1998). Danko and Dečman (2019) and Wu (2008) also report that affective strategies were the least used ones. Danko and Dečman suggest that the role of affective strategies was more obvious at lower levels of proficiency.…”
Section: Literature Reviewmentioning
confidence: 97%
See 3 more Smart Citations
“…Bremner finds that compensation and metacognitive strategies were used most of all, while affective and memory strategies were the least used ones (1998). Danko and Dečman (2019) and Wu (2008) also report that affective strategies were the least used ones. Danko and Dečman suggest that the role of affective strategies was more obvious at lower levels of proficiency.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Thus, it can be concluded that affective, cognitive, social and partly metacognitive approach are not formulated into language learning strategies. Meanwhile, the Companion Volume of New Descriptors (Council of Europe; 2018) replaces the descriptors of four language skills and lists appropriate strategies for carrying out the language tasks to be accomplished (Danko & Dečman, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The researcher did not make any changes to the instruments as it is considered as standardized instrument with high level of validity. It was proven and adopted in various research around the world as well (Danko & Dečman, 2019;de Zarobe & Smala, 2020;M. Lestari & Wahyudin, 2020;Nesrine Aoudjit, 2018;Park & Kim, 2017;Ranjan et al, 2021;Saks & Leijen, 2016;Stander, 2020).…”
Section: Research Instrumentsmentioning
confidence: 99%